Analysis of the effect of acupuncture in the treatment of fibromyalgia: literature review. - Sanita, Priscila Contatori Vital de Macedo; Moraes, Taise de Souza Moreira; Santos, Fernanda Mara dos (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Fibromyalgia is characterized by widespread musculoskeletal pain, stiffness, fatigue, sleep and mood disturbances, anxiety and functional changes. With no definitive pathogenesis, it is predominant in women. Its diagnosis is based on clinical examination of 18 standardized points. Of these, 11 must be painful to characterize fibromyalgia. Acupuncture, which aims to balance the body, has been used frequently in studies of pain and treatments. The main risk factors for fibromyalgia related to Chinese Medicine are: invasion of cold wind, emotional stress, irregular diet and excessive physical labor. Objective: Conduct a literature review to determine the effect of acupuncture as a technique to be used for pain relief and improved quality of life in individuals with fibromyalgia. Method: A literature search was performed through the Bireme, Lilacs, Pubmed, Medline and Scielo databases, 2008 - 2012. Results: The review found that acupuncture is an effective form of treatment for individuals with fibromyalgia, but greater methodological rigor needs to be established. Conclusion: Acupuncture can be effective in reducing pain, and in improving sleep and quality of life in individuals with fibromyalgia. However, there is still need for further research to enhance and extend the effective therapeutic use of acupuncture in the treatment of fibromyalgia.